\[\boxed{\text{863\ (863).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = 2 - 4x\]
\[x\] | \[0\] | \[1\] |
---|---|---|
\[y\] | \[2\] | \[- 2\] |
\[1)\ x = 1 \Longrightarrow \ y = - 2\]
\[x = 0 \Longrightarrow \ \ y = 2\]
\[x = - 2 \Longrightarrow \ \ y = 10\]
\[2)\ y = - 4 \Longrightarrow \ \ x = 1,5\]
\[y = - 2 \Longrightarrow \ \ x = 1\]
\[y = 2 \Longrightarrow \ \ x = 0\]
\[3)\ y < 0\ \ при\ \ x > 0,5.\]
\[\boxed{\text{863.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[= (x + 4)\left( x^{2} - 20x + 100 \right) =\]
\[= (x + 4)(x - 10)^{2}\]
\[= \left( 36 - a^{2} \right)\left( - 1 - 2a - a^{2} \right) =\]
\[= (a - 6)(a + 6)(a + 1)^{2}\]
\[3)\ a^{2}(b - 1) - b^{2}(a - 1) =\]
\[= a^{2}b - a^{2} - ab^{2} + b^{2} =\]
\[= ab(a - b) - (a - b)(a + b) =\]
\[= (a - b)(ab - a - b)\]